2020
DOI: 10.1021/acsphotonics.0c00357
|View full text |Cite
|
Sign up to set email alerts
|

Lasing at Multidimensional Topological States in a Two-Dimensional Photonic Crystal Structure

Abstract: Recently, topologically engineered photonic structures have garnered significant attention as their eigenstates may offer a new insight on photon manipulation and an unconventional route for nanophotonic devices with unprecedented functionalities and robustness. Herein, we present lasing actions at all hierarchical eigenstates that can

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…We have also observed light emission from both edge-state and corner-state in a larger-size photonic cavity with reduced coupling between the corners. Very recently, lasing in a single corner has been reported for similar nanopatterned structures 35,36 . Those corner lasers, however, operate at low temperatures 35 or do not show the unique properties of multipolar lasing in coupled corner modes with different field profiles and Q factors 35,36 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have also observed light emission from both edge-state and corner-state in a larger-size photonic cavity with reduced coupling between the corners. Very recently, lasing in a single corner has been reported for similar nanopatterned structures 35,36 . Those corner lasers, however, operate at low temperatures 35 or do not show the unique properties of multipolar lasing in coupled corner modes with different field profiles and Q factors 35,36 .…”
Section: Discussionmentioning
confidence: 96%
“…Very recently, lasing in a single corner has been reported for similar nanopatterned structures 35,36 . Those corner lasers, however, operate at low temperatures 35 or do not show the unique properties of multipolar lasing in coupled corner modes with different field profiles and Q factors 35,36 . In this work, we have conclusively demonstrated the stable multipole corner modes with antinode intensities at two or four corners as a result of coupling between the corners.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the coupled higher-order topological modes can be a useful starting point for higher-order non-Hermitian physics [27,28]. They may also find applications such as topological wave and light confinement [13,29] and topological lasing [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of promising preliminary theoretical considerations 6,22,23 , several experimental studies in dissipative HOTI systems [24][25][26] , as well as the recently demonstrated potential of harnessing tightly localized HOTI corner states for the enhancement of nonlinear processes such as third-harmonic generation 27 , there is only one experimental study at hand, where the evidence of switching into the HOTI phase under the nonlinear action of a homogeneous global pump was reported in electronic circuits 5 . Importantly, to date, research into the wave dynamics of photonic HOTIs in conservative optical systems has been confined to strictly linear conditions, and their extension in the presence of nonlinear self-action has yet to be explored.…”
mentioning
confidence: 99%